Młodzi dorośli wobec własnej przyszłości = Young adults facing their future - Farnicka, Marzanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article presents the results of research carried out among a group of young adults from foster families and their peers from natural families. The main focus of the research was comparing the factors influencing young people`s adaptation. Both groups of young adults, from foster families as well as from natural ones, were compared in relation to creating own aims and own paths of development.
Keywords: młodzi dorośli; rodzinne formy opieki; rodzina zastępcza; rodzina naturalna; perspektywy rozwoju